Phenotype, penetrance, and treatment of 133 cytotoxic T-lymphocyte antigen 4-insufficient subjects - Schwab, Charlotte; Gabrysch, Annemarie; Olbrich, Peter; Patiño, Virginia; Warnatz, Klaus; Wolff, Daniel; Hoshino, Akihiro; Kobayashi, Masao; Imai, Kohsuke; Takagi, Masatoshi; Dybedal, Ingunn; Haddock, Jamanda A.; et al. (The journal of allergy and clinical immunology, 2018)
Background - Cytotoxic T-lymphocyte antigen 4 (CTLA-4) is a negative immune regulator. Heterozygous CTLA4 germline mutations can cause a complex immune dysregulation syndrome in human subjects. - Objective - We sought to characterize the penetrance, clinical features, and best treatment options in 133 CTLA4 mutation carriers. - Methods - Genetics, clinical features, laboratory values, and outcomes of treatment options were assessed in a worldwide cohort of CTLA4 mutation carriers. - Results - We identified 133 subjects from 54 unrelated families carrying 45 different heterozygous CTLA4 mutations, including 28 previously undescribed mutations. Ninety mutation carriers were considered affected, suggesting a clinical penetrance of at least 67%; median age of onset was 11 years, and the mortality rate within affected mutation carriers was 16% (n = 15). Main clinical manifestations included hypogammaglobulinemia (84%), lymphoproliferation (73%), autoimmune cytopenia (62%), and respiratory (68%), gastrointestinal (59%), or neurological features (29%). Eight affected mutation carriers had lymphoma, and 3 had gastric cancer. An EBV association was found in 6 patients with malignancies. CTLA4 mutations were associated with lymphopenia and decreased T-, B-, and natural killer (NK) cell counts. Successful targeted therapies included application of CTLA-4 fusion proteins, mechanistic target of rapamycin inhibitors, and hematopoietic stem cell transplantation. EBV reactivation occurred in 2 affected mutation carriers after immunosuppression. - Conclusions - Affected mutation carriers with CTLA-4 insufficiency can present in any medical specialty. Family members should be counseled because disease manifestation can occur as late as 50 years of age. EBV- and cytomegalovirus-associated complications must be closely monitored. Treatment interventions should be coordinated in clinical trials.